Utility of international store-and-forward teledermatopathology among a cohort of mostly female patients at a tertiary referral center in Afghanistan - A. Ismail, MD; J.R. McMichael, MD; B.K. Stoff, MD, MAB (Wolters Kluwer, 2018)
Background: The variety and complexity of dermatologic diseases in Afghanistan and the associated diagnostic resource constraints have not been previously studied. Moreover, the utility of store-and-forward teledermatopathology in this resource-limited setting has not been investigated. Methods: A retrospective analysis was conducted of 150 store-and-forward teledermatopathology cases that were composed of a clinical history, clinical images, and histologic images that were sent from an academic teaching hospital in Kabul to a dermatology-trained dermatopathologist at Emory University in the United States between November 2013 and June 2017. For each case, the histologic impression of the Emory dermatopathologist was compared with that of the Kabul-based general pathologist and the clinical differential diagnosis and histologic impression of the Kabul-based dermatologist. Results: Eighty-one of the cases that were analyzed were from female patients. The diagnosis after telepathology consultation differed from the first entity in the clinical differential diagnosis in 34.7% of cases. The telepathology consultation refined the Afghan general pathologist's histologic impression 45.5% of the time and the Kabul-based dermatologist's histologic impression 24.3% of the time. A clinically significant difference in care was made in 19.3% of cases for which an analysis could take place between the histologic impressions of the Emory dermatopathologist and U.S.-trained dermatologist. The most common resource constraints that limited a definitive diagnosis were the inability to perform infectious stains and cultures to identify specific pathogens (19.3% of cases) and immunofluorescence studies to confirm autoimmune bullous disease (6.7% of cases). Conclusions: These results highlight the important diagnostic role that teledermatopathology can serve in resource-limited settings such as in Afghanistan.